Application of crowdsourcing in education on the example of eTwinning - Elżbieta Gajek (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave)
While eTwinning is focused on facilitating collaboration among schools in Europe and beyond, the extensive participation of over one million teachers from 44 countries makes the program an extensive educational crowdsourcing activity. In this paper the program which structures the related pedagogical approaches and practices will be analyzed and discussed in light of the crowdsourcing principles. Teachers and students participate in the program voluntarily. All collaborative activities, material production and publication of results which take place online and emphasize language learning fulfil the characteristics of the effective use of crowdsourcing in education. Two kinds of analyses are undertaken, a global analysis of the program features and local analysis of the selected projects. The global analysis relates the crowdsourcing practices to the eTwinning activities. The local analysis is based on the outstanding projects submitted for evaluation for national awards in Poland, further exemplified by activities and reference to the public sites of the projects. The aim of the text is to show that teachers may effectively use crowdsourcing in educational practice even when not primarily focused on its application.